Introduction and Preservation of Culture through Multimedia-Based Folk Songs Learning in Elementary Schools - Adib Muhammad; Moh Rusnoto Susanto (Indonesian Journal of Primary Education, 2022)
The purpose of this research; (1) to describe the process of learning folk songs through the use of multimedia media. (2) the effectiveness of using learning videos in learning folk songs. The subjects of this study were class 2A students at SDIT Ar-Raihan. The current generation of the nation's successors must not forget their national identity through love and pride in culture as a form of representation of nationalism. It is necessary to develop a sense of belonging, love and pride in culture, one of which is folk songs, especially in elementary schools, where currently the subject matter of folk songs has been included in the learning of Cultural Arts and Crafts (SBdP).But in fact, there are very few SBdP learning hours. For this matter, a special strategy is needed so that the learning objectives are achieved. The strategy is to utilize multimedia learning media in the form of videos to learn folk songs. Data collection techniques using observation, interviews, and documentation. Data analysis technique using triangulation. The results of this study indicate that; (1) Utilization of learning videos can make it easier for students to learn folk songs entitled 'Ampar-Ampar Pisang' and 'Apuse'. (2) The use of videos can be very effective in changing the pattern of interest and eventually love folk songs. So that students can get to know, grow a sense of belonging, foster a sense of love, and contribute to preserving regional culture.